Digital Enterprise Design and Management 2013 Proceedings of the First International Conference on Digital Enterprise Design and Management DED&M 2013 - Benghozi, Pierre-Jean.; Krob, Daniel; Rowe, Frantz; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book contains all refereed papers that were accepted to the first edition of the « Digital Enterprise Design & Management » (DED&M 2013) international conference that took place in Paris (France) from February 12 to February 13, 2013. (Website: http://www.dedm2013.dedm.fr/) These proceedings cover the most recent trends in the emerging field of Digital Enterprise, both from an academic and a professional perspective. A special focus is put on digital uses, digital strategies, digital infrastructures and digital governance from an Enterprise Architecture point of view. The DED&M 2013 conference is organized under the guidance of the CESAMES non profit organization (http://www.cesames.net/). and benefits from the support of the "Innovation and Regulation of Digital Services" Chair (Orange, Ecole Polytechnique and Telecom ParisTech) and of the "Complex Systems Engineering" Chair (Dassault Aviation - DCNS - DGA - Thales - Ecole Polytechnique - ENSTA ParisTech – Telecom ParisTech).
From the Contents: Use Case: Business Intelligence "New Generation" for a "Zero Latency" -- Organization (when decisonal & operational BI are fully embedded) -- The Enterprise as the Experiential Design Platform -- From a strategic view to an engineering view in a digital enterprise. The case of a multi-country Telco -- GrammAds: Keyword and Ad Creative Generator for Online Advertising Campaigns -- Interoperable Systems and Software Evolution: Issues and Approaches.
Keywords: Computational intelligence; Engineering economics; Engineering economy; Computational Intelligence; Engineering Economics, Organization, Logistics, Marketing